Educator perceptions on teaching Indigenous health: Racism, privilege and self‐reflexivity. - Vass, Alyssa; Adams, Karen (Medical Education, 2021)
Introduction: General practitioners (GPs) and family medicine clinicians should respond to Indigenous peoples' health needs. However, medical graduates feel underprepared for this work. The foundational elements of racism, white privilege and cultural self‐reflexivity remain conspicuously absent from medical education in general practice programmes, despite inclusion in curriculum frameworks. This study explored the perception and experiences of Australian GP educators in teaching this content. Methods: We undertook a qualitative study that gathered data through semi‐structured interviews with GP educators (n = 12) at a medical school in Victoria, Australia. We utilised the Reflection learning domain of the Aboriginal and Torres Strait Islander Health Curriculum Framework to shape interview questions on racism, white privilege and cultural self‐reflexivity. Data were analysed from constructivist and Critical Indigenous Theory paradigms to formulate key themes. Results: General practitioner educators were challenged by Reflection content, struggled to articulate a refined pedagogy for provision of anti‐racist, self‐reflexive learning and felt poorly qualified to teach Indigenous health, articulating preference for delegation of teaching to Indigenous peoples. They simultaneously stated the importance of inclusion of Reflection teaching in general practice, alongside expressing beliefs that appeared to devalue its perceived relevance. Students were perceived as being either disinterested or incapable of Reflection learning, or conversely, more engaged than previous generations with these topics. Discussion: The results call into question how skilled are GP educators to teach elements of Indigenous health education such as racism, white privilege and cultural self‐reflexivity. Unskilled educators can reinforce colonialism in curricula, including through minimisation of content. Stronger anti‐racist pedagogy is urgently required in medical education. Vital to this is active research on educator preparedness, evidence‐based teaching models and accountable curriculum accreditation. Vass and Adams explain why stronger anti‐racist pedagogy is urgently required in medical education through examination of knoweldge and expertise related to Indigenous health content.